2020
DOI: 10.3390/nu12072010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Plant-Based Dietary Patterns on Cancer-Related Outcomes: A Rapid Review and Meta-Analysis

Abstract: Long-term cancer survivors represent a sizeable portion of the population. Plant-based foods may enhance the prevention of cancer-related outcomes in these patients. We aimed to synthesize the current evidence regarding the impact of plant-based dietary patterns (PBDPs) on cancer-related outcomes in the general population and in cancer survivors. Considered outcomes included overall cancer mortality, cancer-specific mortality, and cancer recurrence. A rapid review was conducted, whereby 2234 original a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 82 publications
(295 reference statements)
2
46
0
Order By: Relevance
“…In the case of B12, dietary intervention studies are currently lacking, which warrants investigation. A limited amount of studies have reported no significant reduction in cancer mortality in vegans and vegetarians [214], who likely have decreased B12 serum levels due to lack of meat consumption. However, many vegan and vegetarian individuals take B12 supplements to maintain B12 serum levels.…”
Section: Dietary Interventions Of One-carbon Metabolismmentioning
confidence: 99%
“…In the case of B12, dietary intervention studies are currently lacking, which warrants investigation. A limited amount of studies have reported no significant reduction in cancer mortality in vegans and vegetarians [214], who likely have decreased B12 serum levels due to lack of meat consumption. However, many vegan and vegetarian individuals take B12 supplements to maintain B12 serum levels.…”
Section: Dietary Interventions Of One-carbon Metabolismmentioning
confidence: 99%
“…The vegetarian diet seems to decrease the overall cancer risk [ 151 ]. In a case-control study including 469 subjects, Chang et al (2017) observed a lower risk of breast cancer in vegetarians [ 152 ].…”
Section: Link Between Nutrition Periodontitis and Other Main Chromentioning
confidence: 99%
“…A pesco-vegetarian diet reduced the risk of colorectal cancer [ 155 ]. In contrast to these results, a review by Molina-Montes et al (2020) explained that due to the low number of studies available (five studies included), it was not possible to conclude that a vegetarian diet had a preventive role on the overall incidence of cancer [ 151 ].…”
Section: Link Between Nutrition Periodontitis and Other Main Chromentioning
confidence: 99%
“…Conversely, the Mediterranean diet is recognized as one of the healthiest diets mainly thanks to the large use of extra-virgin olive oil, vegetables, and fruits ( Martinez-Gonzalez et al, 2015 ). Furthermore, it has been reported that the adoption of a vegan/vegetarian diet is associated with a decreased risk of cardiovascular diseases ( Kim et al, 2019 ; Molina-Montes et al, 2020 ), but also with an increase in haematological diseases ( Mcevoy et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%